1990
DOI: 10.1111/j.1365-3016.1990.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and smoking at 3 months postpartum by lactation history

Abstract: A spontaneous decrease in maternal drinking and smoking often occurs during pregnancy. The present study was conducted to determine if these lower levels of maternal drinking and smoking during pregnancy persist into the postpartum period, and if so, to determine if they are related to breastfeeding. Drinking and smoking were estimated in three cohorts of postpartum women who had been followed since pregnancy. The first group never breastfed their infants; the second group breastfed for less than 1 month; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
6
27
0
1
Order By: Relevance
“…This finding is consistent with a previous study that found that women who breast-fed were less likely to report heavy episodic drinking (Little et al, 1990). Possible explanations for this finding are that women who engage in risky drinking may choose not to breast-feed to avoid the potential transmission of alcohol to their child, or women drinkers may be less likely to breast-feed their child because of a potential effect of alcohol on lactation.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with a previous study that found that women who breast-fed were less likely to report heavy episodic drinking (Little et al, 1990). Possible explanations for this finding are that women who engage in risky drinking may choose not to breast-feed to avoid the potential transmission of alcohol to their child, or women drinkers may be less likely to breast-feed their child because of a potential effect of alcohol on lactation.…”
Section: Discussionsupporting
confidence: 91%
“…Eight articles provided data sufficient to calculate odds ratios and their standard errors; for 5 others, the authors provided the necessary data.These 13 studies [6][7][8][9][10][11][12][13][14][15][16][17]29 composed the metaanalysis. Maternal smoking was assessed during the pregnancy in 7 studies and after delivery in 6 studies.All but 1 of the 13 studies were conducted in developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…(evidence level-NHMRC III-2) investigated the relationship between levels of maternal smoking and drinking of 463 women at preconception, during pregnancy, and in the postpartum period. 8 Approximately 80% reported drinking some alcohol in the month before conception, with alcohol use dropping after conception, and only 40% of subjects reporting drinking in the last trimester. After delivery, drinking rose and by the end of the third month postpartum, 69% of the total sample reported some drinking, however, not to the level reported at preconception.…”
Section: Lactational Performancementioning
confidence: 99%
“…Little et al (1990) 8 Investigated levels of maternal drinking and smoking (n = 463) women prior to, during and post pregnancy. Women breastfeeding at three months postpartum reported less drinking, and less binge drinking than women who never breastfed or breastfed for less than one month.…”
Section: Iii-2mentioning
confidence: 99%
See 1 more Smart Citation